PERAN HATA PODA DAN UMPASA DALAM UPACARA ADAT BATAK TOBA TERHADAP PENDIDIKAN KARAKTER - Eva Solina Gultom; Arman Arman (KABANTI : Jurnal Kerabat Antropologi, 2019)
This study explains about how hata poda/ advices and umpasa/ parables or hopes as part of local wisdom that mostly found in Batak Toba traditional ceremonies work to building the characters of receivers by the presence of Ulos. Hata poda and umpasa are not hastily given and it should concern about the social position of the giver (Ulos) based on Dalihan na Tolu. Dalihan na Tolu is a philosophy of life hold by Batak Toba society consisting of Hula-hula (the highest), dongan sabutuha, and boru (the lowest). Hata poda and umpasa assumed as an instrument/ media of communication containing of advices and hopes/prayers delivered by the highest rank (parents or elders) to their descendant. This study uses textual analytical description to answer all problems which may emerge. The terms of hata poda and umpasa found in Batak Toba traditional ceremonies possess positive values to generating the characters and behaviors of the receivers which mostly dominated by youngsters. Forms of Batak Toba traditional ceremonies are the wedding, birth ceremony, death ceremony, baptism and others.